Web and wireless geographical information systems : 17th International Symposium, W2GIS 2019, Kyoto, Japan, May 16-17, 2019, proceedings /: 17th International Symposium, W2GIS 2019, Kyoto, Japan, May 16-17, 2019, proceedings. (2019) - Unknown
No abstract available